HUBUNGAN DUKUNGAN KELUARGA DENGAN POLA PEMBERIAN ASI PADA BAYI USIA 0 sampai 6 BULAN - Adelia Laksmita Dewi Supriyanto; Shinta Kristianti; Suwoyo Suwoyo (Poltekkes Kemenkes Malang, 2021)
Breastmilk has many ingredient that are important for child development. The pattern of breastfeeding can be divided into exclusive and non exclusive. Person behavior in breastfeeding is influenced by many factor that shape health behavior, one of them is family support. This literature study aims to determine the relationship between family support and breastfeeding pattern in 0 until 6 month infant age. The method of writing scientific papers uses literature studies. Literature sources use articles with the process of searching text books , journals, scientific articles, literature review from the year of 2015 to 2020. The result of this literature study indicate a relationship between family support and breastfeeding pattern in 0 until 6 month infant age. Thus the researcher found that family support affect the pattern of breastfeeding, mothers who get support from the surrounding environment, there are husband, parent, and other families will be in a state of calm and have positive thoughts towards the baby so that the mother feels happy when she sees the baby, then think of the baby with great affection and want to give exclusive breastfeeding to the baby.